2008
DOI: 10.1124/jpet.108.145581
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Oral Absorption of Cyclosporine A after Liver Ischemia-Reperfusion Injury in Rats: The Contribution of CYP3A and P-Glycoprotein to the First-Pass Metabolism in Intestinal Epithelial Cells

Abstract: The bioavailability of orally administrated cyclosporine A (CsA) is poor and variable in liver transplantation recipients. Little information is available about the effect of liver ischemia-reperfusion (I/R) injury, which is associated with liver transplantation, on the intestinal first-pass metabolism of CsA. In the present study, we investigated the pharmacokinetics of CsA after liver I/R and assessed the effect of liver I/R via CYP3A and P-glycoprotein (P-gp) on its intestinal first-pass metabolism. When Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Our previous studies demonstrated that the expression levels of P-gp in the upper, middle, and lower small intestine were significantly increased after liver I/R (Ikemura et al, 2009(Ikemura et al, , 2012. Therefore, we first evaluated the mRNA expression levels of the two distinct genes encoding the rat P-gp, Mdr1a (Abcb1a) and Mdr1b (Abcb1b), in the small intestine of Sham and I/R rats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies demonstrated that the expression levels of P-gp in the upper, middle, and lower small intestine were significantly increased after liver I/R (Ikemura et al, 2009(Ikemura et al, , 2012. Therefore, we first evaluated the mRNA expression levels of the two distinct genes encoding the rat P-gp, Mdr1a (Abcb1a) and Mdr1b (Abcb1b), in the small intestine of Sham and I/R rats.…”
Section: Resultsmentioning
confidence: 99%
“…Liver I/R model rats were prepared according to our previous report (Ikemura et al, 2009). Briefly, after the rats were anesthetized by intraperitoneal injection of 50 mg/kg pentobarbital, partial hepatic ischemia was achieved by clamping the blood vessels of the left portal vein and hepatic artery using a microvessel clip.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is likely that the expression and function of these transporters are altered after the liver IR injury. Indeed, the limited data available in the literature (7)(8)(9)(10) suggest that the mRNA and protein levels of the canalicular transporters P-glycoprotein (P-gp) and multidrug resistance-associated protein 2 (Mrp2) may be altered by warm hepatic IR injury. However, the effects of the injury on the functions of these canalicular transporters with respect to the biliary excretion of drugs remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…18,29) Furthermore, radixin has been just recently proposed to play a crucial role in regulating the membrane localization and functional activity of P-gp in the small intestinal by using mice lacking radixin. 32) Since the small intestinal P-gp acts as a first barrier against the absorption of various substrate drugs administered via the oral route, [33][34][35][36][37][38] it seems to be important to accumulate the evidence with regard to the regulatory factors for the plasma membrane localization of P-gp. However, there has been no direct evidence investigating the molecular interaction between P-gp and radixin in the small intestine and the role of radixin in the alteration mechanism of P-gp.…”
mentioning
confidence: 99%